2014
DOI: 10.5539/ass.v11n3p26
|View full text |Cite
|
Sign up to set email alerts
|

Self-extension and Purchase Behavior of Dog Related Products and Services: An In-depth Interview among Selected Malaysian Dog Owners

Abstract: This paper discusses the findings of an explorative study among selected Malaysian dog owners who regard their dogs as extended-self and their purchase behavior of dog related products and services. A qualitative research was conducted to gain some deeper insights on purchase behavior of dog related products and services, an under research area. The study aimed to determine whether these dog owners consider their dogs as an extension of their selves and describe their purchase behavior. In-depth interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Appendix 3 No mediation/ moderation tested This study examines the effects of separation from the i-Phone on self, cognition, anxiety, and the physiology of its users. It was revealed that when the iPhone users were unable to answer their ringing iPhone, their heart rate and blood pressure increased, feelings of anxiety and unpleasantness increased, and self-reported extended self and cognition decreased Cheong and Yi (2015) Qualitative paper…”
Section: Consumers' Digital Selfextensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix 3 No mediation/ moderation tested This study examines the effects of separation from the i-Phone on self, cognition, anxiety, and the physiology of its users. It was revealed that when the iPhone users were unable to answer their ringing iPhone, their heart rate and blood pressure increased, feelings of anxiety and unpleasantness increased, and self-reported extended self and cognition decreased Cheong and Yi (2015) Qualitative paper…”
Section: Consumers' Digital Selfextensionmentioning
confidence: 99%
“…Self-extension can happen in both the real and digital worlds (Belk, 2013). The role of self-extension has been explored in the real world by studying how individuals incorporate a brand (Sprott et al , 2009), a smartphone (Ross and Bayer, 2021), or even a pet (Cheong and Yi, 2015) into their self-concept. These relationships with brands have also been studied in the SNS context (Rabbanee et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous homes now keep dogs, fish, rabbits, and even snakes as pets, and they do so for a variety of reasons, including because they are charming and cuddly and because they may reveal a person's personality. Several owners of these animals are prepared to part with a significant sum of cash to keep and care for them (Cheong & Yi, 2015). The majority of pet owners view their animals as members of the family and unique friends who fill the roles of buddy and listener in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Tais sentimentos fazem com que os donos de animais de estimação se aproximem cada vez mais de seus pets. E se encontrem dispostos a consumir e gastar, uns mais que outros, por produtos e serviços para seus animais (BELK, 1996;HOLBROOK, 2008;LUE;PANTENBURG;CRAWFORD, 2008;BOYA et al, 2012;CHEONG;YI, 2015;KIRK, 2019;SCHLEICHER;CASH;FREEMAN, 2019). Nesse sentido, compreender o comportamento de compra de donos de animais é cada vez mais crítico para o marketing (KUMCU; WOOLVERTON, 2015).…”
unclassified